Adherence to ketoacids/essential amino acids-supplemented low protein diets and new indications for patients with chronic kidney disease. Issue 1 (December 2016) - Fouque, Denis; Chen, Jing; Chen, Wei; Garneata, Liliana; Hwang, SJ; Kalantar-Zadeh, Kamyar; Kopple, Joel; Mitch, William; Piccoli, Giorgina; Teplan, Vladimir; Chauveau, Philippe
Abstract Background Low protein diets (LPD) have long been prescribed to chronic kidney disease patients with the goals of improving metabolic abnormalities and postpone the start of maintenance dialysis. Methods We reviewed the recent literature addressing low protein diets supplemented with ketoacids/essential aminoacids prescribed during chronic kidney disease and their effects on metabolic, nutritional and renal parameters since 2013. Results We show new information on how to improve adherence to these diets, on metabolic improvement and delay of the dialysis needs, and preliminary data in chronic kidney disease associated pregnancy. In addition, data on incremental dialysis have been reviewed, as well as potential strategies to reverse protein energy wasting in patients undergoing maintenance dialysis. Conclusion These recent data help to better identify the use of low protein diets supplemented with ketoacids/essential aminoacids during chronic kidney disease.